Desigualdade educacional e cultura digital no ensino remoto durante o isolamento social: percepções de discentes do ensino médio da região do Bico do Papagaio-TO (2020-2021) - Rosa, Cristiane de Oliveira (2024)
The general objective of the work is to identify and analyze the perceptions of public high school students about the consequences of remote teaching during the Covid-19 pandemic in the Bico do Papagaio region, Tocantins, focusing on educational and social inequalities. The specific objectives are: to verify the relationship between remote teaching and students' living conditions; raise public educational policies adopted during the pandemic; and analyze changes in performance indicators (Ideb and Enem) in Tocantinópolis, Palmeiras do Tocantins and Nazaré, with an emphasis on students' perceptions of educational inequality and integration of digital culture during the period of social isolation. The research, supported by the Coordination for the Improvement of Higher Education Personnel (Capes), uses a qualitative-quantitative methodology to explore the experiences and perceptions of students from selected schools, addressing nuances related to access to education and technology in a context of health emergency global. The dissertation contextualizes the educational scenario in the North region, marked by socioeconomic disparities and limited access to digital resources, revealing how the pandemic exacerbated pre-existing inequalities. The study analyzes the historical and social context of the Bico do Papagaio region, considering the educational policies of the state of Tocantins and the implementation of remote teaching. Using questionnaires as a data collection instrument, the research seeks to capture students' perceptions of the inequalities generated or intensified by remote teaching, including issues of access to technology, quality of internet connection and adequacy of pedagogical content to the new educational reality. The conclusions of the dissertation highlight the urgency of more effective public policies, capable of addressing both educational inequalities and the challenge of promoting an inclusive integration of digital culture in teaching. The research investigates the impact of remote teaching in high school in vulnerable areas, aiming to improve pedagogical practices to promote equity and digital inclusion. The findings suggest the need for future research on the long-term impact of remote learning, access and use of technology in education, educators' perceptions, public policy analyses, and educational infrastructure, emphasizing the importance of investigating these aspects to improve education during crises.